A GLIMPSE/CASE STUDY OF ELDERLY PEOPLE AT A SENIOR CITIZEN HOME IN PAKISTAN - PARVEEN, CHAGANI; SOBIA, IDREES; MISBAH, ZAFAR (i-Manager's journal on nursing, 2020)
The elderly population is considered a vulnerable group as they become dependent on others for their routine activities and care. The majority of the elderly population has been neglected in many of the developed and developing countries. However, providing them with a shelter home does not always facilitate quality of life. They need holistic care to live a healthier and peaceful life with dignity. A Case study design was utilized to determine the need assessment of the elderly people living in senior citizen homes. The study was conducted in a senior citizen home situated in one of the metropolitan cities of Pakistan. Elderly people aged 60 years and above living in this home were included in the study. A total of 380 people, 200 males and 180 females were registered with this home. In order to collect the data, a naturalistic observation method was used in the study. As per the findings of the study, the majority of the participants were unaware of the health practices particularly, diet, exercise, regular health checkup etc. The management and staff were not trained in elderly care in the home. Policy makers need to realize the significance of awareness sessions for elderly people. The and management of senior citizen homes should be trained for taking care the elderly people. Higher authorities must be kept in loop for conducting appropriate training sessions and regular health screening of the elderly people.